Treatment Outcomes of Pregnant Women with COVID-19 Infection in Roi Et Hospital - สมศรี, ศิริกัญญา (Srinagarind Medical Journal, 2022)
Background and Objective: Pregnant women with severe symptoms of COVID-19 infection are associated with an increased risk of perinatal complications. This study was undertaken to determine the treatment outcomes of pregnant women infected with COVID-19. Methods: This study was a retrospective descriptive study collecting data from medical records of 68 pregnant women with RT-PCR confirmed for COVID-19 and delivered 18 cases, including data of 19 newborns at Roi Et Hospital during January-September 2021. Data were analyzed using descriptive statistics. Results: During January-September 2021, there were 68 pregnant women infected with COVID-19 admitted in Roi Et Hospital, 50 cases undelivered and 18 cases delivered. The pneumonia was found 80% in the undelivered group, as for 83.34% in the delivered group. The most common clinical symptoms were fever (66.76%), cough (55.56%) and pneumonia (83.34%). In the delivered group had 17 newborns delivery by cesarean, 17 newborns were cured and one died. There were 19 newborns, as one mother twins delivered. The mean gestational age was 37.26 weeks (S.D.2.91), mean birth weight was 3,058.94 g. There were no cases of COVID-19 infection among these newborns but one case was birth asphyxia and one newborns died after birth. Conclusion: A total of 68 pregnant women were found infected with COVID-19 and most of them were cured with only one case has severe infection and died. The results of treatment included 18 delivered, 19 newborns and 1 neonatal death.